Pengembangan Kurikulum Pembelajaran Bahasa Arab di Masa Pandemi Covid-19 - Ayu Desrani; Dzaki Aflah Zamani (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2021)
Purpose- this study aims tofind out and analyze the appropriate curriculum in Arabic learning during the covid-19 pandemic, where at this time the covid-19 pandemic is increasing and its spread is growing rapidly, so it becomes a challenge for a teacher to overcome the learning so that it continues as it should. , including learning Arabic. Design/Methodology/Approach- This study used a qualitative approach with a library research method that used books and other literatures as the main object. This research was analyzed descriptively on the content to provide a clear, objective, systematic, analytical and critical description and description of the appropriate Arabic language learning curriculum during the COVID-19 pandemic. Findings- 4 basics in the development of the Arabic language learning curriculum during the pandemic: 1) the preparation of learning objectives must be adapted to the circumstances of students and socialized to parents to work together to achieve these goals. 2) the content or material content is designed in such a way as to get students to lead to higher order thinking skills. 3) During the learning process the teacher is required to be as creative as possible to guide learning, the use of appropriate methods and media is very influential. 4) evaluation based on project is highly recommended to avoid the possibility of students cheating on each other. Research Limitation/Implications- This study cannot cover all in detail about Arabic language skills, because in essence during the current COVID-19 pandemic, teachers need more ways in which subject matter can be conveyed properly to students. However, this study can provide a comprehensive picture of the needs of Arabic language teachers in teaching, one of which is the use of learning technology.